Juegos lúdicos como medio de solución al trastorno de hiperactividad con déficit de atención en los estudiantes del 2 año de E.G.B de la Escuela Asilo San José de la parroquia Clemente Baquerizo, cantón Babahoyo de la Provincia de Los Ríos - Guerrero Calero, Diana Carolina (2019)
This research work is entitled "Playful Games as a means of solving the hyperactivity disorder with attention deficit in the students of the 2 years of GBS of the school" Asilo San José ", during the course of this research and the practices carried out in This Institution was able to recognize, through observation, the shortcomings and needs of some children with ADHD of the transition degree; from there arises the problematizing question Why the Playful Games are a solution to the Hyperactivity Disorder with Attention Deficit in the students of the 2 years of EGB of the school "ASILO SAN JOSÉ" of the Clemente Baquerizo parish, Babahoyo canton of the province from the rivers? To try to solve this question, the educational-recreational implementation applied to the different areas of the lesson plan was generated as a pedagogical strategy, making the student improve his concentration. The methodology used was of a qualitative and descriptive nature where a solution to the problem was proposed. It was intended that the present project would reduce the lack of attention and hyperactivity, and at the same time it would constitute a contribution to the improvement of the teaching and learning process. This is undoubtedly an excellent pedagogical proposal because it deals with recreational-recreational activities that can be applied to the improvement of attention deficit disorder (ADHD) and, at the same time, is an innovative strategy for the integral teacher.